Comments on detecting rogue taxa using RogueNaRok. Issue 4 (4th July 2017) - Wilkinson, Mark; Crotti, Marco
Abstract : Rogues are relatively unstable taxa in phylogenetic analyses that are of concern if they obfuscate relationships, or support for relationships, of interest among more stable taxa. RogueNaRok is a recently developed heuristic solution to the problem of identifying rogue taxa. We illustrate the performance of RogueNaRok with simple examples designed to clarify its behaviour. We argue that the optimality criterion currently used by RogueNaRok may sometimes be poorly suited to the task of detecting rogues and that the scores reported by RogueNaRok should not be interpreted as measures of taxon instability. We suggest how RogueNaRok might be enhanced and recommend that it not be relied upon exclusively for detecting rogues.